From rebellion to electoral violence: evidence from Burundi - Colombo, A; D’Aoust, O; Sterck, O (University of Chicago Press, 2019)
What causes electoral violence in postconflict countries? The theoretical literature emphasizes the potential role of (1) ethnic grievances, (2) political competition, and (3) specialists in violence. Our study is the first to test these three hypotheses simultaneously. Using a unique data set on electoral violence in Burundi, we study variations in the intensity of electoral violence between neighboring municipalities, relying on the fact that these are more likely to have similar unobservable characteristics. Interestingly, we find that electoral violence did not result from ethnic grievances, which goes against the commonly held view that this factor necessarily plays a key role in violence in the region. Rather, we show that electoral violence is higher in municipalities characterized by acute polarization between demobilized rebel groups, fierce political competition, and a high proportion of Hutu. The effect of political competition is stronger in the presence of numerous demobilized rebels.